THE EFFECTS OF FOREIGN EXCHANGE RATES, STOCK MARKET PERFORMANCE, AND FINANCIAL PERFORMANCE ON STOCK RETURNS, PT BANK RAKYAT INDONESIA, TBK (2014-2023) - Musafa, Musafa (PT. Altin Riset Publishing, 2024)
The research aims to provide insights into the factors driving the variability in the bank's stock returns, utilizing quantitative regression analysis as the primary methodological approach. The background of the study underscores the significance of understanding the diverse factors affecting stock market dynamics, particularly in the context of a prominent Indonesian bank. Financial news sources and historical data from reputable sources like Reuters and Bloomberg were utilized to gather metrics and historical trends relevant to the study. The study also incorporates qualitative insights from industry experts and analysis of business financial records to supplement the quantitative analysis. Results indicate that the variables examined foreign exchange rates, stock market performance, and financial metrics do not significantly explain the variations in PT Bank Rakyat Indonesia, Tbk's stock returns during the study period. The regression analysis reveals low R-squared and adjusted R-squared values, alongside non-significant coefficients for each independent variable. These findings suggest that other factors beyond those considered in this study likely exert a more substantial influence on the bank's stock performance. In conclusion, while the study contributes valuable insights into the specific factors influencing PT Bank Rakyat Indonesia Tbk's stock returns, it also highlights the complexities and limitations inherent in relying solely on traditional financial metrics for predictive purposes. Future research could benefit from exploring additional variables and employing more sophisticated methodologies to enhance understanding and predictive accuracy in stock market analysis.